Investigation of steam jet flash evaporation with solar thermal collectors in water desalination systems. (1st December 2020) - Ezzat, Akram W.; Hu, Eric; Taqi Al-Najjar, Hussein M.; Zhao, Zihui; Shu, Xin
Highlights: Subsonic ejector design is developed for experimental and mathematical investigations. Steam ejector efficiency increased up to 53% at primary steam pressure 2 bar. Efficiency saturation beyond primary steam pressure 2 bar due to velocity limitation. Entrainment ratio is inversely proportional to evaporator and condenser pressures. Effectiveness of the solar thermal collector for the desalination process is assessed. Abstract: Experimental and theoretical studies were carried out to investigate the depressurization induced by steam jet using subsonic steam ejector with flat-plate solar thermal collector. Saline water flash evaporation could be realized by such depressurization in water desalination systems. The most critical component in such systems is the steam ejector nozzle where the Mach number within the ejector is highly influenced by its geometry. The main objective of the research is to evaluate the effect of different operating parameters on evaporation performance which can be specified by two factors; first is the subsonic ejector efficiency governed by the steam entrainment ratio, and second is the percentage gain of distilled water productivity. That goal served an innovative drive for the present work. The experimental test rig was designed and constructed with primary steam pressure (1.25–2.5) bar and temperature (106–127) °C using a controlled boiler, while condenser pressure ranged (0.974–1.0) bar. It was found that ejector efficiency increased up to 53% however the efficiency is saturated beyond primary steam pressure of 2.0 bar due to the sonic velocity limitation. Also, it was noticed that the percentage gain of distilled water productivity using steam ejectors with respect to that using conventional evaporation ranged between 1.0%–5.5%. Based on current collector design considerations implemented in the mathematical model, about 34% of the total thermal energy required for water heating and evaporation during the desalination process can be covered by the solar collector. The error analysis for experimental validation indicated an average value of 22.9%. Finally, it was concluded that the present research could be considered as a good basis for further investigations of solar steam jet flash evaporation in desalination systems.